KONSEP WALI ‘ADHAL DALAM KASUS PENOLAKAN WALI KARENA FAKTOR NASAB: ANALISIS YURIDIS TERHADAP PUTUSAN PENGADILAN AGAMA PALANGKARAYA - Rizqa Ainni, Maisya (Mitsaqan Ghalizan, 2025)
This article provides a juridical analysis of guardians’ refusal based on lineage considerations within the framework of Islamic law and Indonesian positive law through the case study of a decision issued by the Palangkaraya Religious Court. The refusal of a guardian (wali) to permit the marriage of a woman under his guardianship without valid Islamic grounds especially due to differences of social or lineage status constitutes aḍhal behavior that violates the woman’s right to choose her spouse. Using a normative legal approach combined with a case analysis of the court’s decision, this study demonstrates that Islamic law, the Compilation of Islamic Law (KHI), and national legislation provide strong protections for women’s rights, including the use of wali hakim as an institutional remedy for aḍhal guardians. The court’s reasoning confirms that lineage considerations cannot be used as legitimate grounds for rejecting marriage consent. The article concludes that the judiciary plays an essential role in ensuring justice and safeguarding women’s autonomy, while societal reinterpretation is needed to eliminate discriminatory practices in marriage.